Identifikasi Tempat Penyimpanan Sementara Limbah B3 Industri Penggilingan Baja Sidoarjo - Rr. Maulidya Permana; Novirina Hendrasarie (Jurnal Serambi Engineering, 2024)
Hazardous (B3) waste can have a negative impact on the environment. If B3 waste is not disposed of directly into the environment or transported by a third party, it may affect the health of the surrounding community and other living organisms. Furthermore, B3 waste has different properties, sources and characteristics from waste in general, being unstable, reactive, explosive, flammable and toxic. The main activities of PT. X's main activities are steel production, which is supported by sophisticated production equipment, machinery and human resources, but the storage area is from production, office and maintenance activities. The TPS criteria used by PT. X to determine the suitability of B3 waste with TPS that refers to the regulations and with the aim of this activity is to evaluate the temporary storage of B3 waste at PT. X.